2002
DOI: 10.1038/sj.onc.1206040
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the transcription factor Ets-1 is an independent prognostic marker for relapse-free survival in breast cancer

Abstract: The transcription factor Ets-1 regulates the expression of several angiogenic and extracellular matrix remodeling factors, and might be implicated in disease progression of breast cancer. In the present study, the prognostic value of Ets-1 expression was assessed by quantitative realtime fluorescence RT -PCR in 123 sporadic primary breast cancer samples of patients with a median followup time of 62 months. Ets-1 expression levels correlated significantly with VEGF and PAI-1 in the same tissue. In univariate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 18 publications
(16 reference statements)
7
97
3
1
Order By: Relevance
“…For example, Ets1 and Ets2 expression was reportedly elevated in breast tumors. [25][26][27] However, we identified no consistent change in the Ets2 transcript level and found that the Ets1 transcript level was instead lower in breast cancer cells than in normal breast epithelial cells. We showed that this decreased Ets1 expression occurred not only in cell lines, but also in primary breast cancers (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…For example, Ets1 and Ets2 expression was reportedly elevated in breast tumors. [25][26][27] However, we identified no consistent change in the Ets2 transcript level and found that the Ets1 transcript level was instead lower in breast cancer cells than in normal breast epithelial cells. We showed that this decreased Ets1 expression occurred not only in cell lines, but also in primary breast cancers (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…1,2 In this assay, it is mandatory to relate gene expression to the amount of tissue analyzed, that is, to normalize for optimal comparison of expression levels between tissue samples. Inaccurate normalization results in inadequate quantification and spurious conclusions.…”
mentioning
confidence: 99%
“…C‐ets‐1 overexpression has been shown to strongly promote malignant invasiveness of breast cancer cells, which is in line with our findings (Furlan et al ., 2008). Further, it is prognostic marker for poor prognosis of human breast cancer (Span et al ., 2002). The second mechanism of MET regulation by TGFβ1 is related to suppression of miR‐128‐3p which, in turn, directly targets MET , which is in line with Jiang and colleagues non‐small cell lung cancer (Jiang et al ., 2016), and thereby impairs HGF/MET‐mediated cell migration.…”
Section: Discussionmentioning
confidence: 99%